TECHNOLOGY-ENHANCED LEARNING IN SPORTS EDUCATION: A COMPARISON OF SELF-DIRECTED DIGITAL LEARNING AND STRUCTURED COACHING - Eggi Sudajana; Sandy Suardi; Arif Hidayat (Four Son Scholarship, 2026)
Technological advancements in various aspects of life have also had a significant impact on the field of physical education. One of the most noticeable impacts is the adoption of digital training apps that allow students to practice independently outside of class hours. However, although self-directed training apps offer many benefits, structured learning supervised by teachers remains the primary choice for developing students’ skills. It is important to conduct research comparing the effectiveness of these two approaches in improving students’ skills. One of the main objectives of this comparison is to determine whether self-directed training apps yield better results in terms of skill improvement, fitness, and performance compared to more structured training. This study employed a quasi-experimental approach with a split-group design. A total of 30 18-year-old students, who are active in badminton, were divided into two groups. The first group consisted of 15 students who engaged in self-directed training using a digital training app, while the second group consisted of 15 students who participated in structured training supervised by a coach. This study showed that the use of a self-directed training app had a significant positive impact on improvements in technical skills, speed, muscle strength, and flexibility, compared to structured training.